EMC3‐EIRENE Simulation of Impurity Transport in Comparison with EUV Emission Measurements in the Stochastic Layer of LHD: Effects of Force Balance and Transport Coefficients. Issue 6 (24th June 2016) - Dai, S.; Kobayashi, M.; Kawamura, G.; Morita, S.; Oishi, T.; Zhang, H. M.; Huang, X.L.; Feng, Y.; Wang, D. Z.; Suzuki, Y.; the LHD experiment group
Abstract: The transport properties and line emissions of the intrinsic carbon in the stochastic layer of the Large Helical Device have been investigated with the three‐dimensional edge transport code EMC3‐EIRENE. The simulations of impurity transport and emissivity have been performed to study the dedicated experiment in which the carbon emission distributions are measured by a space‐resolved EUV spectrometer system. A discrepancy of the CIV impurity emission between the measurement and simulation is obtained, which is studied with the variation of the ion thermal force, friction force and the perpendicular diffusivity in the impurity transport model. An enhanced ion thermal force or a reduced friction force in the modelling can increase the CIV impurity emission at the inboard X‐point region. Furthermore, the impact of the perpendicular diffusivity Dimp is studied which shows that the CIV impurity emission pattern is very sensitive to Dimp . It is found that the simulation results with the increased Dimp tend to be closer to the experimental observation. (© 2016 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)